Mathematical model of the intraocular pressure dynamic - Švitra, Donatas; Vilkytė, Ramunė (Lietuvos matematikos rinkinys, 2013)
In this article the authors performed of the intraocular pressure dynamic mathematical model described one differential equation with delay depends on the search solution, i.e. the Intraocular pressure linear, nonlinear and numeric analyses. Linear analysis was performed D-segmentation method. In the nonlinear analysis was constructed a stable periodic solution application on the bifurcation theory. In the numeric analysis of the intraocular pressure dynamic obtained Runge–Kutta IV series method was compared with the experimental data. Dynamic of the intraocular pressure was calculated applying program “Model Maker”.